Triangular microstrip stacked antenna for dual band operation - Vasistha P.; Vishvakarma B.R. (My University, 2025)
Experimental investigations conducted on triangular microstrip stacked antenna (TMSSA) to achieve dual band operation by optimizing the number of elements reveal that TMSSA attains the maximum -10 dB return-loss band of 688.6 MHz for (1+3) structure for second resonance. The air gap spacing of 2.5 mm in (1+1) structure improved -10 dB return-loss (RL) band by 612.14 MHz as compared to 242.3 MHz for zero spacing in first resonance (frl). It is also observed that -10 dB return-loss band depends heavily on the angular rotation (non-alignment) in the (1+1) structure.